Rancang Bangun Sistem Informasi Penjualan Barang Berbasis Web di Toko Kelontong Haji Agus - Abdul Aziz Permana; Miki Wijana (INTERNAL (Information System Journal), 2023)
Sales Information System Design is made to make it easier to manage goods at the Grocery Store, the previous transaction recording process was still using a manual system, making it difficult to know the stock of goods, errors occurred in recording and it was slow in making sales transaction reports. This research was made based on the descriptive method approach in collecting data and information needed to implement objects in a systematic, factual, accurate and in accordance with the facts. As for system design using the OOAD (Object Oriented Analysis Design) method with the UML (Unified Model Language) model. This website is implemented using the PHP programming language (Hypertext Preprocessor) and stored using a MySQL database, Web Server using Xampp and Visual Studio Code. The results showed that Haji Agus Grocery Store can increase the efficiency and productivity of grocery stores in managing transactions, stock of goods and others and can provide information in real time.